CLASSROOM MANAGEMENT STRATEGIES BASED ON PRINCIPLES OF EDUCATIONAL PSYCHOLOGY - Prasetio Rumondor; Suhari Suhari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Effective classroom management is essential in creating a conducive and productive learning environment. Based on the principles of educational psychology, successful classroom management strategies include a deep understanding of individual student characteristics, the application of positive reinforcement techniques, and the provision of constructive feedback. In addition, establishing a safe and inclusive learning environment by setting clear rules and routines, as well as good time management, is essential to reduce disruptive behaviour and improve student concentration. This process should be dynamic and adaptive, requiring ongoing evaluation and reflection to keep the strategies relevant and effective. With a holistic and student-centred approach, teachers can improve student motivation, participation and learning outcomes, and create an optimal educational experience for all learners.